Rheumatology nurses’ knowledge and practices on pain management - Pehlivan, Seda; Özer, Serap (The European Research Journal, 2024)
Objective: Nurses have important responsibilities in providing effective pain management. This study was conducted to determine the level of knowledge and practices of rheumatology nurses regarding pain management. Methods: A descriptive study sample was 64 nurses in the rheumatology clinic. Data were collected using the Nurse Introduction Form and Questionnaire on Knowledge and Practices Regarding Pain Management. The data were evaluated in the SPSS. Results: It was determined that 73.4% of the rheumatology nurses did not receive training on pain management. The pain management knowledge score was moderate, and the knowledge of non-pharmacological pain management was insufficient. The mean pain management self-confidence score was 6.03±2.01 (0-10), and a positive correlation was found between the graduation year, working years in rheumatology, and pain management knowledge score (P<0.05). Findings showed that the rheumatology nurses wanted to receive training on non-pharmacological interventions in pain management, pain-related psychosocial issues, and pain diagnosis. Conclusion: Most of the participating rheumatology nurses did not receive training on pain management; their knowledge was only moderate, and they wanted to receive more training. As nurses’ working years increased, the pain management self-confidence score increased. It is important to ensure orientation in the clinic by providing training to nurses who start to work in the rheumatology clinic regarding management and non-pharmacological interventions.